Changes in cerebral tissue oxygen saturation during anaesthetic‐induced hypotension: an interpretation based on neurovascular coupling and cerebral autoregulation1. (24th April 2013) - Meng, L.; Gelb, A. W.; McDonagh, D. L.
Summary: There is currently no consensus regarding how to intervene in anaesthetic‐induced hypotension. Whether or not the balance between cerebral oxygen supply and demand is maintained lacks adequate elucidation. It is thus intriguing to explore how cerebral tissue oxygen saturation is affected by anaesthetic‐induced hypotension. Thirty‐three patients scheduled for elective non‐neurosurgical procedures were included in this study. Physiological measurements were performed immediately before induction with propofol and fentanyl and after tracheal intubation. Mean (SD) Bispectral index decreased from 84.3 (9.3) to 24.4 (8.0) (p < 0.001). Mean arterial pressure decreased from 84.4 (10.6) mmHg to 53.6 (11.4) mmHg (p < 0.001). However, cerebral tissue oxygen saturation remained stable (67.0 (9.4) % vs 67.5 (7.8) %, p = 0.6). These results imply that the fine balance between cerebral oxygen supply and demand is not disrupted by anaesthetic‐induced hypotension. An interpretation based on neurovascular coupling and cerebral autoregulation is proposed.